Densitometria ossea: una breve guida per il nefrologo - Francesco Iannuzzella; Giulio Pioli; Mariarosa Maiorana; Mariacristina Gregorini (AboutScience Srl, 2019)
Studies in patients with chronic kidney disease have definitively shown that "dual-energy X-ray absorptiometry" (DXA) may be helpful in assessing fracture risk. Moreover, it is essential to diagnose osteoporosis and evaluate response to treatment. In order to obtain the best utility from DXA, nephrologists need to know the fundamentals of this technique, its indications in clinical practice, and the potential pitfalls in the interpretation of its results. This review will provide an overview of the fundamentals, methodology, and current clinical applications of DXA with special focus on the nephrologist's perspective.